Use of a Doubly Robust Machine-Learning–Based Approach to Evaluate Body Mass Index as a Modifier of the Association Between Fruit and Vegetable Intake and Preeclampsia. Issue 8 (30th March 2022) - Bodnar, Lisa M; Cartus, Abigail R; Kennedy, Edward H; Kirkpatrick, Sharon I; Parisi, Sara M; Himes, Katherine P; Parker, Corette B; Grobman, William A; Simhan, Hyagriv N; Silver, Robert M; Wing, Deborah A; Perry, Samuel; et al.
Abstract: The Dietary Guidelines for Americans rely on summaries of the effect of dietary pattern on disease risk, independent of other population characteristics. We explored the modifying effect of prepregnancy body mass index (BMI; weight (kg)/height (m) 2 ) on the relationship between fruit and vegetable density (cup-equivalents/1, 000 kcal) and preeclampsia using data from a pregnancy cohort study conducted at 8 US medical centers ( n  = 9, 412; 2010–2013). Usual daily periconceptional intake of total fruits and total vegetables was estimated from a food frequency questionnaire. We quantified the effects of diets with a high density of fruits (≥1.2 cups/1, 000 kcal/day vs. <1.2 cups/1, 000 kcal/day) and vegetables (≥1.3 cups/1, 000 kcal/day vs. <1.3 cups/1, 000 kcal/day) on preeclampsia risk, conditional on BMI, using a doubly robust estimator implemented in 2 stages. We found that the protective association of higher fruit density declined approximately linearly from a BMI of 20 to a BMI of 32, by 0.25 cases per 100 women per each BMI unit, and then flattened. The protective association of higher vegetable density strengthened in a linear fashion, by 0.3 cases per 100 women for every unit increase in BMI, up to a BMI of 30, where it plateaued. Dietary patterns with a high periconceptional density of fruits and vegetables appear more protective against preeclampsia for women with higher BMI than for leaner women.